CYBERWISER.eu: Innovative Cyber Range Platform for Cybersecurity Training in Industrial Systems - Varano, Dario; Dini, Gianluca; Basile, Mariano (Electronic Communications of the EASST, 2021)
Information technologies are nowadays part of industrial systems. Employees in charge of managing these systems typically have little or very little knowledge of cybersecurity. In this work we initially explore the challenges related to cybersecurity training in industrial systems and then we propose an approach based on CYBERWISER.eu cyber range platform. A cyber range provides a multipurpose virtual environment in which organisations can test critical capabilities and reveal how effectively they integrate people, processes, and technology to protect their strategic information, services, and assets. By facilitating high-fidelity simulations, a cyber range can associate the cybersecurity training phase with a personalized security testing, together with a unit testing, on different kind of systems, including SCADA.